Percolation Threshold of AOT Microemulsions with n-Alkyl Acids as Additives Prediction by Means of Artificial Neural Networks - Moldes, Óscar A; Astray, Gonzalo; Cid, Antonio; Iglesias-Otero, Manuel A; Morales, Jorge; Mejuto, Juan C (Tenside Surfactants Detergents, 2017)
Different artificial neural networks architectures have been assayed to predict percolation temperature of AOT/iC(8)/H2O microemulsions in the presence of n-alkyl acids with a chain length between 0 and 24 carbons, using a multilayer perceptron with five easy-acquired entrance variables (number of carbons, log P, length of the hydrocarbon chain, plc, and acid concentration). The evaluation of the neural networks was carried out by means of RMSE and IDP, resulting that the architecture with better results consists in five input neurons, two middle layers (with five and ten neuron respectively) and one output neuron. Results prove that Artificial Neural Networks are a useful tool elaborating models to predict percolation temperature of microemulsion systems in the presence of additives.
Keywords: microemulsion; electrical percolation; prediction; artificial neural network (ANN); AOT; organic acid; JCR; Scopus